In-service fatigue cracking of the propeller shafts joined by a spline-pinned construction to the engines of AN-24, AN-26, and IL-18 aircrafts - A. Shanyavskiy; A. Toushentsov (Fracture and Structural Integrity)
The paper delivers a critical review of the research data on the crack initiation and crack growth patterns characteristic of the components of the spline-bolted joints between the propeller shaft and reducer shaft at An-24, An-26, and Il-18 aircrafts. Cracks in the shafts nucleated because of reduced bolt-fastening force. Actually, the bolt (bolts) failed first (also by fatigue) and then fatigue cracks nucleated and grew in the shafts, the spline surface fretting zones and/or sharp edges of the attachment (bolt-conducting) holes making the crack origin sites. The crack growth history shows itself through the regular Macro-Beach Marks, each mark sequentially pointing to the next loading event of the propeller shaft, i.e., to each next flight. The cracks cease growing for some while in the airscrews and their shafts just replaced to another aircraft. For the airscrew shafts, the critically assessed data show the crack growth period Np ranging as five to ten percent of a total running period Nf . We recommend performing nondestructive inspection of the airscrew shafts on every 250- hour running period to ensure the safety flights.